Archbishop Mečislovas Reinys: Personal Case No. 3145 of Prisoner Mečislovas Reinys - Vasiliauskienė, Aldona (Genocidas ir rezistencija, 2011)
This article, for the first time for the Lithuanian academic community and all parties concerned, presents the case of Archbishop Mečislovas Reinys (3 February 1884–8 November 1953) from the archives of Vladimir Prison. The personal case No. 3145 of Reinys is the last key source in the study of the life of the archbishop while he was imprisoned far away from his native land in 1948–1953.The article also mentions other sources which are important for studying the process of how Archbishop Reinys became a ‘state criminal’. These sources include documents such as the memoirs of the archbishop’s contemporaries and of Dr Gotthold Starke, who spent a year in prison together with Reinys; Reinys’ letters to occupying authorities and humorous writings reflecting the moods at that time; Reinys’ letters from Vladimir Prison to his sister Julijona Reinytė-Martinėnienė (1878–1960), who was the only one to avoid deportation to Siberia; and materials from Reinys’ files stored in the Lithuanian Special Archives (LYA, f. K-1, ap. 58, b. P-14999; ap. 45, b. 771).In 2010, the Ministry of the Interior of the Russian Federation provided the author of this article with an opportunity to familiarise herself with the case of Archbishop Reinys. It is this case that this article is dedicated to. This case is a continuation of the study ‘Archbishop Mečislovas Reinys: letters from Vladimir Prison’, which was published in Genocidas ir rezistencija (Genocide and Resistance) magazine in 2005, and expanded and supplemented with the case materials of Vladimir Prison, from which the archbishop sent his letters.The author of the article classified the documents of the case in ten groups, each of which are comprehensively studied in the article.The case in question expands our knowledge about the last years of the life of Archbishop Reinys, allows identifying the precise date of his death and time of his burial (the place of burial remains unknown) at the town cemetery of Vladimir, located in the vicinity of Vladimir Prison. Documents available from the case testify to Archbishop Rainys’ deep faith and trust in God.
Keywords: Soviet occupation; Catholic Church; Mečislovas Reinys; repressions